Efektivitas Pemberian Edukasi Kesehatan Terhadap Tingkat Kecemasan Pasien Gagal Ginjal Kronis yang dihemodialisa di RSKG Ny. Ra Habibie Bandung - Lisbet Octovia Manalu; Nia Nur Latifah; Ahmad Arifin (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Hemodialysis is a therapy for CRF patients to replace kidney function by using an artificial kidney in the form of a dialysis machine. Hemodialysis patients will experience lifelong dependence, this will lead to changes in imbalances in their life, these changes will cause physical and psychological problems, one of which is anxiety. Anxiety in CRF patients is a response to the threatening situation experienced by CRF patients and is a normal thing that occurs accompanied by developments, changes and new experiences in his life. Health education is a planned effort to influence others in doing what is expected. The aim of this reasearch is to determine the effect of providing health education on the level of anxiety in patients with chronic renal failure during hemodialysis at RSKG Ny. Ra Habibie Bandung. The methods of this research is a pre-experimental research design with one-group pre-post test design approach. The number of samples in this study were 60 respondents using purposive sampling technique. Using the Wilcoxon statistical test the results obtained p-value of 0.00 with a significance of p <? (0.05), p-value of 0.00 <0.05